Development of Neuroregenerative Gene Therapy to Reverse Glial Scar Tissue Back to Neuron-Enriched Tissue - Zhang, Lei; Lei, Zhuofan; Guo, Ziyuan; Pei, Zifei; Chen, Yuchen; Zhang, Fengyu; Cai, Alice; Mok, Gabriel; Lee, Grace; Swaminathan, Vishal; Wang, Fan; Bai, Yuting; et al. (Frontiers in Cellular Neuroscience, 2020)
Nerve injury often causes neuronal loss and glial scar formation. We have recently demonstrated NeuroD1-mediated direct conversion of reactive glial cells into functional neurons in adult mouse brains. Here, we further investigate whether such direct glia-to-neuron conversion technology can reverse glial scar back to neural tissue in a severe stab injury model of the mouse cortex. Using adeno-associated virus (AAV)-based gene therapy approach, we ectopically expressed single neural transcription factor NeuroD1 in reactive astrocytes in the injured areas.We discovered that the reactive astrocytes were efficiently converted into neurons both before and after glial scar formation, and the remaining astrocytes proliferated to repopulate themselves.The astrocyte-converted neurons were highly functional, capable of firing action potentials and establishing synaptic connections with other neurons. Unexpectedly, expression of NeuroD1 in reactive astrocytes resulted in a significant reduction of toxic A1 astrocytes, together with a significant decrease of reactive microglia and neuroinflammation. Furthermore, accompanying the regeneration of new neurons and repopulation of new astrocytes, new blood vessels emerged and blood-brain-barrier was restored. These results demonstrate an innovative neuroregenerative gene therapy that can directly reverse glial scar back to neural tissue, opening a new avenue for brain repair after injury.• Glial scar can be reversed back to neural tissue through neuroregenerative gene therapy• Astrocytes are not depleted after neuronal conversion• Neuron to glia ratio after injury can be rebalanced through in vivo cell conversion• Conversion of reactive astrocytes into neurons reduces neuroinflammation• Astrocyte-to-neuron conversion restores blood vessels and blood-brain-barrierBrain repair, brain injury, NeuroD1, astrocyte-to-neuron conversion, in vivo reprogramming, neuron to astrocyte ratio, neuroinflammation, blood-brain-barrier